Evaluation of selected phytochemical content of freshly harvested tomato and tomato-based products - Afolake, Sunmonu, Basirat; Olubunmi, Akinsola, Akinjide; Oyeyemi A., Idowu, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The health benefits of tomato have make tomato and its derived products a perfect alternative choice as functional food. The study was carried out to evaluation selected phytochemical contents of freshly harvested tomato and tomato-based products. Freshly harvested tomato and four tomato-based products were analyzed using standard methods. Data were analyzed using computer software for one-way analysis of variance, while Duncan multiple range test (DMRT) was used to separate means where there is a significant difference. Range of values obtained for phenol, flavonoid, lycopene, and titrable acidity of the samples were 354.42 to 2047.29 mg/kg, 315.98 – 1452.30 mg/kg, 212.18 to 500.79 mg/kg, and 15.93 – 53.19ml/kg. The results showed that tomato-based commercial products are indeed richer in selected phytochemical investigated than freshly harvested tomato.